The influence of shopping lifestyle, fashion involvement, and hedonic shopping on e-commerce and moderating effect of impulse buying / Vicky Brama Kumbara … [et al.] - Kumbara, Vicky Brama; -, Muhammad Ridwan; Mohd Kodri, Aida Nur; Muhamad Hanapiyah, Zulkefli (2023)
This study aims to determine how shopping lifestyle, fashion involvement and hedonic shopping influence the e-commerce and the moderating role of impulse buying. This study was utilized a quantitative research approach and questionnaires was used as a data gathering technique. The population of this study is the customers that used an e-commerce platform. The number of sample size for this study is 50. SPSS was used for the data analysis and this study was used reliability analysis and regression analysis to answer all the objective. The finding shows hedonic shopping has a significant influence on e-commerce Platform. However, shopping lifestyle and fashion involvement are not influencing the e-commerce platform. The finding also presents a moderating effect of impulsive buying on the relationship between independent and dependent variable. The finding shows the small moderation interaction effect between the variable. The limitation of this study is a small number of sample size. This study is important in understanding the customer shopping style and it will help the business in strategies their marketing activities. This study present a finding that will help the enterprise in strategies their business for sustain.